Water Supply and Regulation of Underground Reservoir in Coal Mine considering Coal-Water Occurrence Relationship. (22nd January 2022) - Chi, Mingbo; Cao, Zhiguo; Li, Quansheng; Zhang, Yong; Wu, Baoyang; Zhang, Bao; Yang, Yi; Liu, Xiaoqing
Abstract : Water supply prediction and control is one of the key issues in exploitation of coal mine underground reservoirs (CMUR). In order to investigate the water supply for underground reservoirs in coal mines, the aquifers were classified into three types (types I, II, and III) according to the relative location of aquifers. The discrete element fluid structure coupling numerical simulation model is constructed according to the classification results. The numerical simulation parameters are inversed based on the surface subsidence data and the advance support pressure, and then, the disturbed characteristics and water pressure variation law of different types of aquifers are studied. The research results show that the maximum water inflow of type III, type II, and type I aquifers is 739 m 3 /h, 377 m 3 /h, and 279 m 3 /h, respectively. The dynamic calculation process of underground reservoir capacity under mining disturbance is refined, and the regulation and storage methods of underground reservoir are preliminarily put forward.